The Role of Epigenetic Modifications in Neurotoxicity Induced by Neonatal General Anesthesia - Ma, Lin-Hui; Yan, Jing; Jiao, Xin-Hao; Zhou, Cheng-Hua; Wu, Yu-Qing (Frontiers in Molecular Neuroscience, 2022)
It has been widely demonstrated by numerous preclinical studies and clinic trials that neonates receiving repeated or long-time general anesthesia could develop prolonged cognitive dysfunction. However, the definite mechanism remains largely unknown. Epigenetics, defined as heritable alterations in gene expression that are not a result of alteration of DNA sequence, includes DNA methylation, histone post-translational modifications, non-coding RNAs and RNA methylation. In recent years, the role of epigenetic modifications in neonatal general anesthesia-induced neurotoxicity has been widely explored and reported. In this review, we discuss and conclude the epigenetic mechanisms involving in the process of neonatal anesthesia-induced cognitive dysfunction. Also, we analyze the wide and broaden prospects of epigenetics in this field and its possibility to work as treatment target.